2018
DOI: 10.4236/ojpathology.2018.81001
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Induced Cancers in Africa: Epidemiology and Carcinogenesis Mechanisms

Abstract: The resurgence of infectious diseases on the African continent plays a major role in the increase in cancer occurrence. Whereas in developed countries the causes of occurrence of cancers are related mainly to non-infectious factors; cancers of infectious origin become a dramatic particularity in Africa. The proportion of virus-induced cancers may reach up to 75% of cancer cases in certain countries. Oncogenic viruses such as human papilloma virus (HPV), hepatitis viruses B and C, human herpes virus 8 and Epste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The protonated sites are shown in Figure 5. These are the nitrogen atoms sp 2 of benzothiazole ring (N1) and sp 3 PA and GB both account for basicity strength of a site in molecule. For these six benzothiazoles, these two quantities agree on basicity forces of sites examined.…”
Section: Protonic Affinity and Basicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The protonated sites are shown in Figure 5. These are the nitrogen atoms sp 2 of benzothiazole ring (N1) and sp 3 PA and GB both account for basicity strength of a site in molecule. For these six benzothiazoles, these two quantities agree on basicity forces of sites examined.…”
Section: Protonic Affinity and Basicitymentioning
confidence: 99%
“…Cancers constitute on planetary scale a public health concern. If the epidemiological data show a decrease in mortality rate linked to this pathology in Western countries, these are expanding in developing countries [1][2][3][4][5]. Scientific studies have shown that the most common cancers in the sub-Saharan region are prostate, cervical, breast, ovarian and liver cancers [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Epstein Barr virus (EBV) is a ubiquitous gamma-herpesvirus from the family of primate lymphocryptovirus (LCVs) [1]. EBV primarily infects B lymphocytes and epithelial cells [2] and over 90% of the global human population have contracted EBV by adulthood and carry the latent virus lifelong [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Cancers associated with viral infections are on the rise globally, and in SSA [ 18 , 21 ] ( Figure 1 ). Approximately a third of all cancers in Africa are linked to a viral etiology [ 22 ]. Viruses such as HPV are generally dependent on the cellular machinery of the host for replication [ 18 ].…”
Section: Introductionmentioning
confidence: 99%